The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.14569/ijarai.2012.010406
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Melakarta Raaga Identification Syste: Carnatic Music

Abstract: Abstract-It is through experience one could as certain that the classifier in the arsenal or machine learning technique is the Nearest Neighbour Classifier. Automatic melakarta raaga identification system is achieved by identifying the nearest neighbours to a query example and using those neighbours to determine the class of the query. This approach to classification is of particular importance today because issues of poor run-time performance are not such a problem these days with the computational power that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(2 reference statements)
0
6
0
Order By: Relevance
“… Chronologically, they are sampurna raaga -they contain all seven swaras of the octave in both upword and downword scale [1][2].  They are also known as krama sampurna raaga -that is the sequence is strictly ascending and descending in the scales, without any jumps or hap harard notes [9].…”
Section: Rules For Melakartamentioning
confidence: 99%
See 3 more Smart Citations
“… Chronologically, they are sampurna raaga -they contain all seven swaras of the octave in both upword and downword scale [1][2].  They are also known as krama sampurna raaga -that is the sequence is strictly ascending and descending in the scales, without any jumps or hap harard notes [9].…”
Section: Rules For Melakartamentioning
confidence: 99%
“…These features are given to (i) GMM (Gaussian Mixture Model) [1] (ii) HMM (Hidden Markov Model) [2] (iii) KNN (K-Nearest Neighbor) with Cosine distance (iv) KNN with Earth Mover Distance (EMD) [3][4] for training and testing the system. …”
Section: Technical Work Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The precision values varied from 26% to 72% for the different feature classes. More work on genre classification was reported by Norowi et.al, [9] [10] presented an overview of techniques for Nearest Neighbor classification that placed focus on mechanisms for finding distance between neighbors using Cosine Distance, Earth Movers Distance and formulae were used to identify nearest neighbors and algorithms for classification in training and testing in order to identify Melakartha raga in Carnatic music. From the derived results it was concluded that Earth Movers Distance produced better results than Cosine Distance measure.…”
Section: Literature Surveymentioning
confidence: 99%